A New Measure of Rural Access to Transport : Using GIS Data to Inform Decisions and Attainment of the SDGs - Iimi, Atsushi (World Bank, Washington, DC, 2016)
In rural areas of the developing world, where the majority of the poor live, good transport connectivity through road infrastructure and transport services is an essential part of the enabling environment for sustainable growth. A lack of detailed nationwide data has limited previous efforts to develop measures of access to roads in rural areas that would guide policy and investment. The World Bank, with support from DFID, has been piloting a methodology that exploits advances in digital technology to assess population distribution and infrastructure location and quality. The resulting Rural Access Index (RAI) may serve as a useful and cost effective tool for governments planning their rural transport programs and as an indicator of progress towards the achievement of several of the UN Sustainable Development Goal (SDG) targets.